Fatal outcome in a liver transplant recipient with COVID-19 - Huang, Jiao-Feng (Am J Transplant, 2020)
Liver injury is common in patients with COVID-19, but little is known about its clinical presentation and severity in the context of liver transplant. We describe a case of COVID-19 in a patient who underwent transplant 3 years ago for hepatocellular carcinoma. The patient came to clinic with symptoms of respiratory disease; pharyngeal swabs for severe acute respiratory syndrome coronavirus 2 were positive. His disease progressed rapidly from mild to critical illness and was complicated by several nosocomial infections and multiorgan failure. Despite multiple invasive procedures and rescue therapies, he died from the disease. The management of COVID-19 in the posttransplant setting presents complex challenges, emphasizing the importance of strict prevention strategies.